Empirical Evidence of Multicultural Learning Model Effectiveness in Improving Student Learning and Cultural Cohesion in Isolated Toraja Communities (Architecture Image Studies, 2025)
The objective of this study is to know the effect of the use of the Multicultural Learning Model on increasing the learning capacity of students in isolated areas, Bau Village, Tana Toraja and its Impact on Strengthening Local Community Institutions. This study uses a mixed approach that combines surveys, interviews, and learning model development. The research employed pre-experimental studies to assess the effectiveness of multicultural learning models, alongside case studies and observational methods to explore their impact on local institutions in Toraja. Respondents included students, teachers, parents, and community leaders. Research instruments used were academic tests, classroom observations, and interviews. Data was analyzed using descriptive and inferential statistics, including t-tests to compare student performance, and qualitative thematic analysis to identify patterns in respondents' perceptions of the model’s impact. The study confirms that the multicultural learning model improves the learning capacity of students in Bau Tana Village is in line with previous research which shows that an inclusive educational approach to local culture is essential in increasing participation, motivation, and learning achievement in often marginalized areas. Moreover, multicultural education can be a powerful tool to strengthen a sense of togetherness, increase community participation, and build a close relationship between education and cultural heritage.